1994
DOI: 10.1002/ijc.2910570520
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of metastasis of lewis lung carcinoma by a synthetic peptide within growth factor‐like domain of urokinase in the experimental and spontaneous metastasis model

Abstract: Four synthetic peptides (residues 20-30 and 17-34) within the growth factor-like domain (GFD) of murine and human urokinase-type plasminogen activator (uPA) were examined to determine whether they inhibit production of experimental and spontaneous lung metastasis by murine Lewis lung carcinoma (3LL) cells. In an in vivo experimental metastasis assay, which determines mainly the later steps of the metastatic migration process (extravasation from the bloodstream and then growth into pulmonary tumor), none of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
43
1

Year Published

1997
1997
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 85 publications
(44 citation statements)
references
References 15 publications
0
43
1
Order By: Relevance
“…Most approaches have focused on using linear or cyclic peptides based on the sequence of the growth factor domain of uPA [110,111]. Despite the promise of such peptides, their usefulness in vivo remains to be established.…”
Section: Inhibition Of Upa-upar Interactionsmentioning
confidence: 99%
“…Most approaches have focused on using linear or cyclic peptides based on the sequence of the growth factor domain of uPA [110,111]. Despite the promise of such peptides, their usefulness in vivo remains to be established.…”
Section: Inhibition Of Upa-upar Interactionsmentioning
confidence: 99%
“…9 In another study, intraperitoneal injections of peptides from murine ATF inhibited both primary tumor growth and dissemination. 10 Disruption of cell surface uPA/uPAR also inhibited bFGF-or VEGFinduced angiogenesis in an artificial bFGF-enriched extracellular matrix model. 6 In this study, we have used xenograft and syngeneic murine models to assess the antitumoral effects that follow local or systemic administration of a defective adenovirus expressing a secretable uPAR antagonist of murine origin (AdmATF).…”
Section: Introductionmentioning
confidence: 97%
“…Among them, the amino-terminal fragment of urokinase (ATF) is of particular interest because it can also exert a direct effect on the tumor cells and inhibit metastasis in experimental models. [9][10][11] Urokinase and its high affinity receptor, a GPI-anchored membrane protein (CD87), are believed to be critical elements in tumor biology because they control cell motility, tissue remodeling and the bioavailability of angiogenic factors. For example, uPA/uPAR complex formation at the cell surface is required for efficient activation of plasmin, a wide range protease that can degrade components of the basement membrane and the extracellular matrix (eg vitronectin, laminin, fibronectin), a prerequisite for tumor cell invasion.…”
Section: Introductionmentioning
confidence: 99%
“…In our study, there was no evidence of any haemorrhagic complications or derangement of coagulation parameters. Furthermore, there was no skin irritation at the injection site unlike reports involving other u-PA inhibitors (Kobayashi et al, 1996). Mice that received WXC-340 before LPS administration and subsequently daily subcutaneous WXC-340 (0.3 mg kg À1 ) had significantly lower numbers of tumour nodules (A), lung weight (B) and lung-to-body weight ratio (C) than control animals receiving daily PBS ( @ ; Po0.05).…”
Section: Discussionmentioning
confidence: 94%
“…Mimetics of the growth factor-like domain of u-PA inhibit experimental and spontaneous metastases in a murine model of lung cancer (Kobayashi et al, 1996) and u-PAR antagonists inhibit primary tumour growth and angiogenesis in syngenic mouse models (Min et al, 1996). A recently developed selective u-PA inhibitor, WX-UK1 impaired development of lung metastases in a rat model of spontaneous metastatic orthotopic breast adenocarcinoma, whereas Ertongur et al (2004) demonstrated that this compound inhibited in vitro tumour cell Matrigel invasion by a variety of human cancer cell lines (Setyono-Han et al, 2005).…”
mentioning
confidence: 99%